Transcultural fandom of the Korean Wave in Latin America: through the lens of cultural intimacy and affinity space. (July 2019) - Min, Wonjung; Jin, Dal Yong; Han, Benjamin
This article has examined how the Hallyu phenomenon is integrated into a transnational global cultural landscape, focusing on Chilean reception of K-pop. It analyzed how Hallyu fans engage with a social media-saturated environment in Chile, mapping out transnational pop cultural flows within the digital media environment through which the participatory culture of media users is spread. What is interesting is that Chilean society, in general, shows negative attitudes toward K-pop fans. More importantly, while many Chileans consider K-pop fans weird and strange, often disparaging their family members and friends for liking such music, the marginalization of K-pop fans in Chile promotes a greater sense of bonding among them through the affinity spaces of social media. Under this circumstance, most of our interviewees explained that digital media plays a vital role in the dissemination of K-pop in Chile and Latin America. Unlike Hallyu fans in other regions, K-pop fans in Chile have developed cultural intimacy specific to digital site-media, primarily in the realm of social media, and K-pop generates the creation of affinity spaces via different social media platforms.